Pelindungan Hukum Bagi Konsumen Terhadap Layanan Perusahaan Daerah Air Minum (PDAM) Di Kota Samarinda : PELINDUNGAN HUKUM BAGI KONSUMEN TERHADAP LAYANAN PERUSAHAAN DAERAH AIR MINUM (PDAM) DI KOTA SAMARINDA - Afrilia Intan Kurniati (Jurnal Media Justitia Nusantara, 2025)
This research intends to analyze legal protection for consumers regarding the services of the Regional Drinking Water Company (PDAM) in Samarinda, which are often complained about, both in terms of quality and service continuity. In this context, the research evaluates consumer rights as required by Law No. 8 of 1999 on Consumer Protection. Based on a juridical-empirical method, the approach used combines legal analysis with actual conditions in the real world. The findings show that although PDAM has made efforts to improve services through the establishment of water management installations and the expansion of the pipeline, there remains a lack of conformity among the services provided and the needs and expectations of consumers as per the applicable legal provisions. Complaints such as distribution disruptions, water quality not meeting standards, and slow complaint handling are the main issues.